2016
DOI: 10.1016/j.cattod.2015.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Direct dimethyl ether synthesis from synthesis gas: The influence of methanol dehydration on methanol synthesis reaction

Abstract: Direct dimethyl ether (DME) synthesis from synthesis gas is studied with regard to potential effects of methanol dehydration on methanol formation and copperbased catalyst performance. For this, the influence of the operating conditions (space velocity, temperature, pressure, time-on-stream and syngas composition) on activity, selectivity and stability of the catalyst was studied and compared for methanol synthesis and direct DME synthesis. The advantage of the direct over the two-step DME synthesis is apparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 39 publications
4
50
0
Order By: Relevance
“…• C and 50 bar, the productivities are generally higher for the CO 2 -rich feed composition compared to the CO-rich composition (Table 4), which agrees with results reported in the literature [70][71][72][73][74]. In preliminary experiments, we observed a decrease in productivity using CO 2 -rich feed at reaction temperatures ≥250 • C. In this context, we refer to Ruland et al [70], who studied CO 2 hydrogenation using a commercial CZA catalyst and reported a decrease in the conversion of CO 2 -rich syngas with increasing temperature.…”
Section: Evaluation Of the Catalytic Activity And Correlation With Masupporting
confidence: 91%
“…• C and 50 bar, the productivities are generally higher for the CO 2 -rich feed composition compared to the CO-rich composition (Table 4), which agrees with results reported in the literature [70][71][72][73][74]. In preliminary experiments, we observed a decrease in productivity using CO 2 -rich feed at reaction temperatures ≥250 • C. In this context, we refer to Ruland et al [70], who studied CO 2 hydrogenation using a commercial CZA catalyst and reported a decrease in the conversion of CO 2 -rich syngas with increasing temperature.…”
Section: Evaluation Of the Catalytic Activity And Correlation With Masupporting
confidence: 91%
“…as alternative catalysts to γ -Al 2 O 3 for both methanol dehydration process and one-pot CO/CO 2 hydrogenation, exhibiting both higher activity (even at lower reaction temperature) and higher resistance to water adsorption than γ -Al 2 O 3 [19][20][21][22][23][24][25][26][27][28][29][30][31] . In this concern, Zhi et al [22] demonstrated via both experimental and theoretical approach, that the inhibitory effect of water during alcohol dehydration over zeolites is related neither to the destruction of acid sites by water (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The optimum temperature for methanol synthesis shifts by dilution of the CZA catalyst from 230 to 250°C, which is well aligned with temperatures reported for methanol and direct DME synthesis in literature. 5,6,26,30,[59][60][61][62][63][64][65][66][67] DME synthesis, however, is far from equilibrium for all catalyst compositions and the DME yield keeps increasing with temperature. 6,68 Despite the fact that the temperature for methanol dehydration is generally higher, 4,27,31,69 direct DME synthesis is often performed at temperatures of around 250°C, 5,6,26,[59][60][61][62] not only because the methanol synthesis is considered to be the rate determining step in direct DME…”
Section: Steam Adsorbentmentioning
confidence: 99%
“…In literature methanol to acidic catalyst ratios of 1 : 1 up to 8 : 1 can be found. 5,6,60,[70][71][72][73][74] The rate limiting methanol synthesis is reason to choose higher amounts of methanol synthesis catalyst. However, Fig.…”
Section: Steam Adsorbentmentioning
confidence: 99%
See 1 more Smart Citation